2019
DOI: 10.1371/journal.pgen.1008267
|View full text |Cite
|
Sign up to set email alerts
|

Artificial selection on GmOLEO1 contributes to the increase in seed oil during soybean domestication

Abstract: Increasing seed oil content is one of the most important breeding goals for soybean due to a high global demand for edible vegetable oil. However, genetic improvement of seed oil content has been difficult in soybean because of the complexity of oil metabolism. Determining the major variants and molecular mechanisms conferring oil accumulation is critical for substantial oil enhancement in soybean and other oilseed crops. In this study, we evaluated the seed oil contents of 219 diverse soybean accessions acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 70 publications
2
70
0
Order By: Relevance
“…, where V G and V E represent genetic and environmental variation, and each term was extracted from the ANOVA results 58 . The mean value of each accession across four years was used in the statistical analysis, and one-way ANOVA was calculated by the least-significant difference (LSD) method 59 .…”
Section: Detection Of the Oil Content Of Peanut Germplasm The Oil Comentioning
confidence: 99%
“…, where V G and V E represent genetic and environmental variation, and each term was extracted from the ANOVA results 58 . The mean value of each accession across four years was used in the statistical analysis, and one-way ANOVA was calculated by the least-significant difference (LSD) method 59 .…”
Section: Detection Of the Oil Content Of Peanut Germplasm The Oil Comentioning
confidence: 99%
“…As an important factor affecting phenotype, QTL × environment interaction may explain one of the reasons why QTLs can not be identified stably in different environments [26,27]. Previously, many studies have shown complex quantitative traits were controlled by both genetic and environmental factors in soybean [19,28,29]. In this study, there were significant differences in phenotypic values across genotypes, years and populations, suggesting that the leaf-related traits and CC are both influenced by the underlying genes, the environment, and different hereditary backgrounds (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because European consumers still prefer GM-free oilseed end products, while the area planted with soybean, the main oilseed crop of the world [1], is more than 80% planted with GM soybean [5], European soybean breeders should focus on creating high-oil GM-free varieties with conventional breeding methods so that they are able to provide high-quality and healthy end products to European consumers. Seed oil content is a complex quantitative trait, controlled by multiple genes and affected by environmental factors [124,133]. The broad-sense heritability of soybean oil content varied considerably in the range between 0.13 and 0.99 [7,[134][135][136] suggesting that trait inheritance is a function of G, E, M and G × E × M. For example, oil content can be in positive correlation with temperature [137,138], but negative linear relationships [139] and quadratic relationships [140] were also reported.…”
Section: Oil Content and Fatty Acid Compositionmentioning
confidence: 99%
“…Of all the reported QTLs associated with oil traits in soybean, only two (cqPro/oil-15, cqPro/oil-20) have been officially confirmed and repeatedly detected in several different populations, both associated with protein and oil contents and each showing opposite additive effect directions for the two traits, which is why identifying an environmentally stable major QTL regulating seed oil content is of crucial importance [100,102,103,155]. Moreover, QTLs directly related to seed oil accumulation in soybean have not been cloned, so the underlying mechanism has not been thoroughly elucidated to date [133]. Although advance in oil content has been achieved over time, further increasing oil content by traditional breeding based on genetic crossing and phenotypic selection may be difficult and inefficient, because of the polygenic nature of oil regulation and the majority of oil-related loci having varying additive, epistatic or QTL × E effects [156][157][158].…”
Section: Oil Content and Fatty Acid Compositionmentioning
confidence: 99%